Designing instructions for active and reflective students in cello class - Murbiyantoro, Heri; Karyawanto, Harpang Yudha; Mahendra, Marda Putra (Edelweiss Applied Science and Technology, 2025)
This study emphasizes the importance of developing a more effective learning model for teaching the cello at Surabaya State University, particularly to address the limitations of traditional methods that often render students passive. The primary aim of this research is to design and evaluate a learning model that combines Active Learning and Reflective Learning strategies to enhance student engagement and deepen their understanding and practical skills. The methodology employed in this study is qualitative, utilizing a case study approach that focuses on gaining an in-depth understanding of students’ experiences with the implemented learning model. Data collection methods included observations, interviews, and students’ reflective journals over the course of one semester. The findings indicate that the application of this model effectively improves students’ comprehension, technical abilities, and reflective skills. Each learning cycle demonstrated significant progress in areas such as connection, association, communication, and reflection, which underscores the model’s success in enhancing students’ competencies in mastering the cello. This research is expected to contribute to the development of more adaptive and interactive music teaching methods and to open new avenues for further research in the field of music education.